The impact of social media activities on brand equity of hijab brands in Malaysia - Siti Maizalaizzah Akma binti Adnan
The objective of this study is to examine the relationships between social media activities and brand equity of hijab brand in Malaysia. Using the consumer-based brand equity (CBBE) model as the theoretical framework, the present study examined five predictor variables namely entertainment, interaction, trendiness, customisation, and perceived risk to explain brand equity as a dependent variable. The primary data was collected using questionnaires, and the questionnaires were administered online through social media channels. Data was analysed using descriptive analysis by SPSS and presented in form of tables. Partial Least Squares (PLS) method in SmartPLS 3.0 was used to conduct an analysis on a sample of 300 respondents. The findings demonstrated that the characteristics of social media activities have an impact on brand equity of hijab brands in Malaysia. Accordingly, entertainment, interaction, trendiness, and customisation positively influenced brand equity of hijab brands, whereas perceived risk has a negative influence on brand equity of hijab brands. Therefore, all the hypotheses in this study are supported.